Miniaturized and Wearable Electrocardiogram (ECG) Device with Wireless Transmission - Sylvester, S. S.; Su, E. L. M.; Yeong, C. F.; Che Harun, F. K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
ECG Holter is a device used to acquire and monitor the user heart rhythm. However, it is available only in a major healthcare facility as it is very costly. The objective of this work is to develop a portable ECG monitoring device with wireless transmission for early arrhythmia detection and personal monitoring. The heart of the device is based on Atmel ATmega328p processor, which acquires user ECG data through Analog Devices AD8232 ECG analog front-end chip. Data captured is stored offline in memory card before it is transmitted wirelessly to a cloud server for analysis purpose. Experiments indicate that the device able to sample the ECG data up to 1000 samples per second and Wi-Fi based transmission serves the best for data transfer to the cloud server. User and physician can easily access the data for viewing and analysis, eliminating the needs for users to travel to the hospital for ECG acquisition.